Effect of infection with hepatitis B virus on the survival outcome of diffuse large B-cell lymphoma in the prophylactic antiviral era - Nuersulitan, Reyizha; Li, Miaomiao; Mi, Lan; Wu, Meng; Ji, Xinqiang; Liu, Yiqi; Zhao, Hong; Wang, Guiqiang; Song, Yuqin; Zhu, Jun; Liu, Weiping (Frontiers in Oncology, 2022)
Patients with lymphoma who are also infected with Hepatitis B virus (HBV) have a poor prognosis. This could be partly explained by the delay or premature termination of anti-tumor treatment because of HBV reactivation. However, there is limited data on the survival outcome of patients HBV-related lymphoma in the era of prophylactic antivirals. Data for 128 patients with HBV surface antigen-positive diffuse large B-cell lymphoma was collected. The median age was 54 years and the ratio of men to women was 1.2:1. All patients received immune-chemotherapy and prophylactic antiviral therapy. The median number of cycles of immune-chemotherapy were six. The overall response rate was 82% with a complete remission rate of 75%. With a median follow-up of 58.4 months, the 5-year progression-free survival and overall survival rates were 75.7 % and 74.7%, respectively. Nine patients experienced HBV reactivation and one experienced HBV-related hepatitis. Patients with low and high HBV DNA loads had comparable survival outcomes. In conclusion, patients with HBV related lymphoma treated with prophylactic antivirals did not have a poorer prognosis compared with non-HBV infected patients.